(untitled) (Revista Apotheke, 2022)
This text presents the experience lived in the year 2020 in the midst of the Covid-19 Pandemic, of the project “En.tries.: education in times of pandemic”, carried out in the supervised curricular internship of the Degree in Visual Arts at the University of the State of Santa Catarina (UDESC). The aforementioned project sought for a depth in the pedagogical and poetic construction that is not always given space in the academy and in the initial teacher training. In this context, the artistic practice, provoked from the experience of oneself, propelled other ways of thinking about teaching, proposing to create a form in action, that is, a form[action], always in becoming. In this continuous movement, marks were produced, shifting the certainties that the students had about teaching and life.